Analisis Dan Perancangan Sistem Informasi Geografis Fasilitas Kesehatan Berbasis Android Pada Kota Jambi - Sukron, Ade; Sarjono, Sarjono (Jurnal Manajemen Sistem Informasi, 2021)
Based on the results of a survey conducted by the author of 20 correspondents from outside the city of Jambi, information was obtained that 70% of people outside the city of Jambi still find it difficult to get information on health facilities in the city of Jambi and also 65% of people outside the city of Jambi are still asking the surrounding community for information. Information on routes, addresses and health facilities in the city of Jambi. Problems like this are a difficult obstacle for the community because they have to spend their time only to find out information on health facilities in the city of Jambi. This research framework consists of problem identification, literature study, data collection, systems analysis, prototype design, and report preparation. This study uses the UML (Unified Modeling Language) modeling tool and produces a prototype that can provide information related to Jambi's health facilities that can be accessed easily using an android-based smartphone.